Peningkatan Resiliensi Psikologis Penyintas Kekerasan Rumah Tangga Melalui Psikoterapi Positif - Abdur Rahman; Kamsih Astuti; Metty Verasari; Izzanil Hidayati; Rifdha Wahyuni (Psyche 165 Journal, 2022)
Domestic violence has a huge impact on survivors who act as wives and husbands as perpetrators of violence. Domestic violence has make survivors trapped in an endless cycle of violence, this is caused by a learned feeling of helplessness and great disappointment towards their partner while still hoping that their partner's behavior changes. The impacts experienced by survivors of domestic violence can be in the form of traumatic experiences, threats, restraints, feelings of helplessness which ultimately lead to maladaptif behavior such as having the belief that they feel helpless in addition to the physical impact they feel. Resilience is needed so they can quickly recover from the experience of violence. In this study, there were five female survivors of domestic violence whose ages ranged from 23-44 years and were still married. We measured the resilience of these participants using a modified Resilience Scale which was built based on the Connor Davidson Resilience Scale 25 (CD-RISC 25) and was given positive psychotherapy intervention to increase their resilience score. The process of measuring resilience in survivors was carried out three times, pre-test, post-test and one week after the intervention was given. Using the Wilcoxon Signed Rank Test as an analytical procedure, it was found a significant effect after being given a positive psychotherapy intervention on survivor's resilience (z=-2.032, p <0.05). Resilience observed increased in survivors is in the form optimistic thinking, increased self-confidence, eliciting positive memories and emotions towards oneself, had a new source of hope and energy to deal with everyday problems.